2010
DOI: 10.1002/ijc.25154
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐test agreement and quantitative cross‐validation of immunochromatographical fecal occult blood tests

Abstract: Immunochromatographical fecal occult blood tests were shown to have higher sensitivity for detecting colorectal neoplasms than the commonly used guaiac-based test. However, positivity rates, sensitivity and specificity vary widely. We aimed to assess the reasons for this heterogeneity. Six dichotomous (qualitative) immunochromatographical tests were used in the same stool samples, taken before cathartic bowel preparation, from 1,330 participants of the German colonoscopy screening program. Positivity rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 20 publications
0
34
0
4
Order By: Relevance
“…Just as for calprotectin as comprehensively documented recently by Ayling, 30 different FIT have different cut-off faecal haemoglobin concentrations to determine positive and negative results. This has been nicely shown by Brenner et al 31 who examined six qualitative FIT and demonstrated that the positivity rates using the same panel of faecal samples varied. Clinical sensitivity and specificity for advanced neoplasia also varied directly and inversely, respectively, with the positivity rate, as expected.…”
Section: Introductionmentioning
confidence: 54%
“…Just as for calprotectin as comprehensively documented recently by Ayling, 30 different FIT have different cut-off faecal haemoglobin concentrations to determine positive and negative results. This has been nicely shown by Brenner et al 31 who examined six qualitative FIT and demonstrated that the positivity rates using the same panel of faecal samples varied. Clinical sensitivity and specificity for advanced neoplasia also varied directly and inversely, respectively, with the positivity rate, as expected.…”
Section: Introductionmentioning
confidence: 54%
“…Für die Spezifität in Bezug auf das Vorhandensein neoplastischer Veränderungen wird allgemein die untere akzeptable Grenze bei 90 % angesehen. Die Ergebnisse von Screening-Studien legen nahe, dass, bei entsprechender Einstellung des Grenzwerts, mit den iFOBTs eine dem gFOBT vergleichbar hohe Spezifität von > 90 % bei zugleich sehr viel höherer Sensitivität erreicht werden kann [142,148]. Diskutiert wird derzeit noch der optimale Hämoglobin-Gehalt, bei dem ein iFOBT als positiv bewertet werden sollte.…”
Section: Level Of Evidence 3aunclassified
“…The values range from 29 to 72% (ref. 13 ), owing to different sampling devices and different stabilities of the haemoglobin extract in the sampling buffer. Additional biochemical markers, such as haptoglobin and transferrin, are sometimes used as a second analyte detected in these test, in order to increase screening accuracy 14,15 .…”
Section: Colorectal Cancermentioning
confidence: 99%